Stratigraphy of the section «Marre-Sale» (West Yamal): analysis with consideration for new data on radiocarbon - O. L. Opokina; E. A. Slagoda; A. N. Kurchatova (Лëд и снег, 2015)
Complex structure of the section across the cape Marre-Sale as well as different approaches to its study are the main reasons for continuation of discussion about the age and genesis of deposits and ground ice. New radiocarbon data complement the previously published information about the age characteristics of upper part of the section. It has been found that the upper strata ices having complex shape occur in layers of different age, while they were formed in the Holocene second half.